Gaya Kepemimpinan Transformasional dan Motivasi Kerja terhadap Kinerja Karyawan: Systematic Literature Review - Bintang Nabila Yudi Putri; Selvi, Evi; Sofiyanti, Neneng (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The purpose of this systematic literature review is to examine whether employee performance is influenced by work motivation and transformational leadership style. Low employee performance in various companies is often associated with ineffective leadership and low motivation. In this review, the PRISMA method was used to conduct a systematic literature search. This study limited the search to journal articles published between 2021 and 2025. The researchers conducted a search in the Google Scholar database and obtained a number of articles. After screening based on title, abstract, and removal of duplicates, only ten articles met the criteria to be used as references in this study. The results of the literature review indicate that most studies found a positive relationship between transformational leadership style and work motivation on employee performance. However, some studies also reported that these two factors did not significantly influence employee performance. These findings provide important insights for organizations in assessing the effectiveness of leadership styles and motivation strategies to enhance employee performance.